2009
DOI: 10.1243/09544097jrrt242
|View full text |Cite
|
Sign up to set email alerts
|

A study of multiple crack interaction at rolling contact fatigue loading of rails

Abstract: The objective of this paper is to investigate geometric and material parameters that affect the interaction of multiple pre-existing (initiated) cracks due to rolling contact fatigue (RCF) loading conditions. In particular, the behaviour of short cracks (head checks) in railway rail is studied. Parameters of interest are initial crack angle and spacing, distribution of initial crack lengths, width of the load/contact zone, and the material properties (in particular, the friction coefficient). Furthermore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…It has been suggested that two small cracks initiated close to each other will interact in a way that only one of them grows, because the other one is left in a less loaded area. This concept is called shielding or crack shielding and simulations made in two‐dimensional cases confirm this . The cracks that have the shortest distance to each other are cracks that are branching.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been suggested that two small cracks initiated close to each other will interact in a way that only one of them grows, because the other one is left in a less loaded area. This concept is called shielding or crack shielding and simulations made in two‐dimensional cases confirm this . The cracks that have the shortest distance to each other are cracks that are branching.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, there has been some critique against this concept . Crack shielding has been mentioned, and simulations have been made with the conclusion that two cracks cannot grow close to each other because they will interact in a way that allows only one of them to grow further because the other one will be shielded . In three dimensions, crack shapes are frequently assumed to be half round or elliptical, which is also yet to be proven.…”
Section: Introductionmentioning
confidence: 99%
“…Previous results [4] reveal that rail head spalling and sub-surface cracks are noticeable within few mm from the rail surface. As discussed in [9], crack originating subsurface regions tend to change direction, mostly either upward towards the rail surface or in some cases downwards. Because of this, the rail head material becomes detached from the surface resulting in spalling, causing failure of the rail.…”
Section: Microstructures Of Damaged Rail Samplesmentioning
confidence: 97%
“…Problem geometry and boundary conditions. effects see for example [23]; however, the simulations in this study is limited to a two dimensional single crack, due to the highly increased complexity associated with the simulation of multiple cracks growing simultaneously. In the figure, also the boundary conditions can be seen (roller supports along three boundaries).…”
Section: Model Assumptions and Discretization Parametersmentioning
confidence: 99%